2017
DOI: 10.3389/fnana.2017.00084
|View full text |Cite
|
Sign up to set email alerts
|

The Human Periallocortex: Layer Pattern in Presubiculum, Parasubiculum and Entorhinal Cortex. A Review

Abstract: The cortical mantle is not homogeneous, so that three types of cortex can be distinguished: allocortex, periallocortex and isocortex. The main distinction among those three types is based on morphological differences, in particular the number of layers, overall organization, appearance, etc., as well as its connectivity. Additionally, in the phylogenetic scale, this classification is conserved among different mammals. The most primitive and simple cortex is the allocortex, which is characterized by the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(140 citation statements)
references
References 37 publications
4
136
0
Order By: Relevance
“…The deep layers V and VI are more developed in the caudal levels (EI, ECC, and ECl) than in the rostral levels (EO, ER, and EL) in the marmoset, with large size and darkly stained cells, a high density of myelin, and the absence of sublayers. In others monkeys, up to three sublayers are described in Layer V: two superficial cellular Layers (Va and Vb) in rats (Witter et al, ) and a deeper, fiber‐rich layer (Vc) in monkeys (Amaral et al, ) and humans (Insausti et al, ). In our preparations, we did not subdivide the deep layers because the lamination pattern was not evident.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The deep layers V and VI are more developed in the caudal levels (EI, ECC, and ECl) than in the rostral levels (EO, ER, and EL) in the marmoset, with large size and darkly stained cells, a high density of myelin, and the absence of sublayers. In others monkeys, up to three sublayers are described in Layer V: two superficial cellular Layers (Va and Vb) in rats (Witter et al, ) and a deeper, fiber‐rich layer (Vc) in monkeys (Amaral et al, ) and humans (Insausti et al, ). In our preparations, we did not subdivide the deep layers because the lamination pattern was not evident.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the organization of the afferent and efferent connections, together with the distributions of AChE and heavy metals and Golgi‐impregnated preparations, Amaral et al () defined seven subdivisions in the monkey EC. Eight subdivisions have been described in the human EC: olfactory, rostral, lateral rostral and caudal, medial intermediate, intermediate, caudal, and caudal limiting (Insausti et al, ; Insausti et al, ). Our parcellation is thus largely consistent with that originally described in M. fascicularis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together with the recent observation that even different regions of the pre/parasubiculum may facilitate distinct forms of mental imagery (Dalton et al, 2018), the current findings provide persuasive evidence that neuroimaging investigations of the hippocampus should, at the very least, differentiate between the pre/parasubiculum and the subiculum proper when investigating contributions of this complex region to human cognition. Indeed, Insausti et al (2017) recently suggested that the concept of a 'subicular cortex' may be incorrect considering it combines the differentiable subicular allocortex (comprising 3 layers) and the pre/parasubicular periallocortex (comprising 6 layers). Our results provide support for this distinction at a functional level.…”
Section: Whole Subfield Analyses -Fc With Cortical Roismentioning
confidence: 99%